Domain wall dynamics in ferromagnetic cylindrical and planar nanostructures - Chandrasekhar Murapaka (2014)
This thesis presents a comprehensive study on domain wall (DW) dynamics in NiFe cylindrical and planar nanostructures. In cylindrical nanowires of relatively low aspect ratio, a three dimensional helical DW is found to separate two vortices of opposite chirality. The formation of helical DW is controlled by introducing geometrical modulations along the nanowire. The magnetic charge calculation at the helical DW shows an abrupt transition between two opposite charges (positive to negative or vice versa). To verify the micromagnetic simulations, compositionally modulated nanowires are grown by pulsed electrodeposition at two different potentials. Differential etching of the two layers of NiFe with different compositions leads to the formation of constrictions. The presence of the helical DWs in the constricted cylindrical NiFe nanowires is verified by magnetic force microscopy (MFM) imaging. At high aspect ratio, transverse DWs that are found in sub-50 nm cylindrical nanowires are shown to possess an intrinsic oscillatory behavior in the translational motion. Moreover, in the absence of external energies, the oscillations are governed by the energy transfer from the DW rotations. Such oscillations are self-sustained and unique to the transverse DWs in cylindrical nanowires. By setting up a magnetostatically coupled nanowire system, an infinite oscillation is achieved by the application of current to balance the DW coupling. The sustained oscillation is analogous to simple harmonic motion between a compressed and relaxed state of the DW. Solving the simple harmonic equation unfolds the finite the mass associated with the DW in cylindrical nanowires which was assumed to be mass less in previous studies. The transverse DW pinning and depinning mechanisms are studied at the geometrical modulations in the planar and cylindrical nanowires. In planar nanowires, DW pinning potential is found to be chirality dependant at an anti-notch structure. The potential barrier undergoes a transition from smooth and gradual to steep and abrupt shape as the dimensions of the anti-notch are varied. In cylindrical nanowires, the DW pinning has shown contrary behaviors with the application of current and magnetic field. Interestingly, an increase in the notch depth results in lowering the depinning current density. The DW deformation and rotation assist the spin-polarized current in depinning process. The degree of DW deformation is higher at the deeper notch and lowers the depinning current density. The DW pinning at the anti-notch has shown two different phenomenon as the height of the anti-notch is varied. At lower dimensions, the pinning mechanism follows the trend similar to the notch. However, at higher dimensions, the DW transformation from transverse to vortex configuration causes the lowering in the barrier height in the field driven case. The barrier potential rises for the current driven case due to the vortex chirality switching within the anti-notch. In planar NiFe nanostructures, the DW injection methods using local Oersted field and the external magnetic field are presented. The key focus is devoted to the transverse DWs in narrow nanowires. Using patterned nanostructures, techniques to control, detect and rectify the DW chirality are presented by using MFM imaging. The selective motion of the vortex core in the presence of the linear magnetic field assists in DW chirality detection. Two different switching mechanisms of the DW within a slanted rectangular structure result in rectifying the chirality of the transverse DW. Finally, a DW based reconfigurable magnetic logic is demonstrated in which a single structure performs all the basic logic operations. Two underlying principles, transverse DW selective switching and the effect of transverse Oersted field on the DW are verified experimentally by MFM imaging.